Arauca: space, conflict and institutionality (2010)
This article tries to picture the relationships present in the convulsed department of Arauca (Colombia), in the fields of geography and space, population and society, politics and conflict, economy and institutionality, illegality and violence, as well as other valid associations among these topics. All this to defend the basic idea that not only the political violence but the conflict, seen in this territory for twenty years, objectively exist, partially linked to the conscious intentionality of the main actors.